The effect of Wedelia biflora leaves extracts on the imflammation cause by allergic reactions of dermatitis in mice (Mus musculus) - . Rinidar; M. Isa; . Sugito (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
The objective of the present study was to investigate useful of Wedelia biflora leaves extracts as  anti allergic caused by dermatitis allergic in mice. A total of 24 males Wistar mices were utilized as experimental animal in this study. The experimental animals were divided into 4 groups, and each group has 4 mices. The first group was a control which was injected with aquades (negative control), while three other groups (group 2 to group 4) were fed with   Wedelia biflora extracts orally at doses of 20 g, 40 g and 60 g per kg body weight, respectively, and the fifth group was a positive control which was injected with 10% ovalbumin, and the last group was given antihistamin drug (Loratadine) as compared control. All of experimental animals were injected with ovalbumin on day 1, 7, and 21, except for  negative control  which were injected with distillated water. The ectracts of Wedelia biflora were fed for 21 days. The inflammation areas were measured using a digital caliper and analysis one-way Anova. The results showed that the treatment of Wedelia biflora were resulted in reducing inflammation size significantly (p0.05) where the dose of 60 g/kg body weight was given the best result compared to other doses due to this value equivalent to antihistamine drug loratadine. We concluded that Wedelia biflora leaves extracts had the anti allergic effect.